Outcomes of microsurgical flap techniques in the reconstruction of extensive lesions due to advanced basal cell carcinoma: a systematic review of complications, recurrence, and aesthetic satisfaction - Pacheco, Elizabeth Arellano; Montenegro, Leidy Daniela Duran; Cobis, Franklin Alejandro Chirinos; Sánchez, Sindy Johanna Álvarez; Bravo, Pedro José Polo; Gómez, Ricardo José Duarte; Zapata, María Camila Rendón (International Journal of Research in Medical Sciences, 2025)
Basal cell carcinoma (BCC) constitutes 70–80% of non-melanoma skin cancers, with an estimated 4.3 million new cases annually in the U.S. Though rarely metastatic, advanced BCC can cause extensive local tissue destruction, particularly in facial regions, necessitating surgical excision followed by complex reconstruction. This study evaluates outcomes of microsurgical flap reconstruction in advanced BCC, with a focus on complications, recurrence, and patient-reported aesthetic satisfaction. A systematic search across six databases until May 2025 identified 263 abstracts, of which 34 full texts were reviewed; nine studies met inclusion criteria. Due to methodological heterogeneity, a narrative synthesis was conducted. Most studies reported low complication rates, with serious issues occurring in fewer than 10% of cases and no significant differences across flap types or age groups. Recurrence rates ranged from 0.22% to 4.4%; notably, 447 lesions treated with narrow margins and frozen section analysis showed a recurrence of only 0.22%. A meta-analysis reported an overall recurrence rate of 2%, with the Muffin technique associated with superior outcomes. Aesthetic results were favorable: OM flaps yielded high satisfaction rates (77.8%, p=0.002) with shorter operative times, and periocular reconstructions demonstrated successful outcomes in 87% of cases, outperforming radiotherapy (69%). However, definitions of "satisfactory" varied across studies. Despite limitations such as inconsistent outcome reporting and short follow-up durations, microsurgical reconstruction in advanced BCC appears safe, effective, and cosmetically satisfactory. OM flaps, in particular, are seen as efficient by both clinicians and patients. Standardized, long-term studies are essential for definitive conclusions.